Képek a magyarországi cigányság 20. századi történetéből : "A világ létra, melyen az egyik fel, a másik le megy" : antropológiai fotóalbum = pictures of the history of gipsies in Hungary in the 20th century : "World is a ladder, which some go up, some go down" : anthropological photo-album - szerk.: Szuhay Péter, Barati Antónia ; tanulmány Szuhay Péter. (Néprajzi Múzeum, 1993)
Includes bibliographical references (p. 361-363) and indexes.